Objectively assessed physical activity and associated factors of sedentary behavior among survivors of stroke living in Cape Town, South Africa. Issue 21 (9th October 2018) - Joseph, Conran; Conradsson, David; Hagströmer, Maria; Lawal, Isa; Rhoda, Anthea
Abstract: Purpose: To investigate objectively measured physical activity in stroke survivors living in low-income areas of Cape Town, South Africa, specifically to: (a) describe the volume of daily physical activity and time spent in different intensity levels and (b) investigate the association of factors covering the International Classification of Functioning, Disability and Health with sedentary behavior. Materials and methods: A cross-sectional design was used, where forty-five ambulatory community-dwelling stroke survivors participated. Volume and intensity of physical activity were assessed with accelerometers for three to five consecutive days. Personal and environmental factors, along with body function and activity, were captured. Multiple linear regression was used to investigate factors associated with the percentage of days spent sedentary. Results: The median number of steps per day was 2393, and of the average 703 minutes of wear time, 80% were spent in sedentary, 15% in light, and 5% in moderate-to-vigorous intensity physical activity. Age, stroke severity, and failing to receive outpatient rehabilitation were independently associated with sedentary, which, taken together, explained 52% of the variance. Conclusions: Low volumes of physical activity and high amount of sedentary time emphasize the need to develop strategies that will increase physical activity. Providing outpatient rehabilitation in a systematic manner post-stroke is a potential target of health care programs in order to reduce sedentary behavior. Implications for rehabilitation: Objectively measured physical activity among community-dwelling survivors of stroke in Cape Town, South Africa was low in volume, and the majority did not meet the recommendations of 150 minutes of at least moderate intensity physical activity. The majority of stroke survivors in South Africa spent most of their time sedentary, which could further increase the risk of cardiovascular impairments. Outpatient rehabilitation should be provided to all patients after stroke since it appears to reduce sedentary time.